Nexus of Social Media Marketing and Small Scale Businesses’ Performance in Buea, Cameroon - Wantchami, Nengieh Lizzie; Ngange, Kingsley Lyonga; Efosi, Babatunde Daphne-Carol (Advances in Social Sciences Research Journal, 2020)
This study examines the connection between social media marketing and small scale businesses’ performance in Buea, Cameroon, by assessing the use of social media for brand and product awareness, sales as well as relationship building. 15 small scale business owners were interviewed through semi structured interview. The results identify a common increase in customers due to social media marketing. They equally reveal that, social media marketing has served as a tool in building brand awareness, customer relationships and reinforcing sales. Findings further indicate that for Small and Medium-sized Enterprise (SME) operators who engage in social media marketing, the benefits far outweigh the cost as they have incorporated promotional strategies and even taken supplies to customers’ door steps. In order to facilitate delivery to customers’ door steps, this study recommends that government should facilitate the creation of a house numbering system to ease door to door supplies of goods purchased online. This study provides some indications for using social media platforms as an ideal method of marketing.